2019
DOI: 10.1021/acscombsci.9b00135
|View full text |Cite
|
Sign up to set email alerts
|

Benzimidazolyl-pyrazolo[3,4-b]pyridinones, Selective Inhibitors of MOLT-4 Leukemia Cell Growth and Sea Urchin Embryo Spiculogenesis: Target Quest

Abstract: 1,3-Substituted pyrazolo­[3,4-b]­pyridinones 11–18 were synthesized by a three-component condensation of Meldrum’s acid with aryl aldehydes and 1,3-substituted 5-aminopyrazoles. Their biological activity was evaluated using the in vivo phenotypic sea urchin embryo assay and the in vitro cytotoxicity screen against human cancer cell lines. In the sea urchin embryo model, 1-benzimidazolyl-pyrazolo­[3,4-b]­pyridinones 11 caused inhibition of hatching and spiculogenesis at sub-micromolar concentrations. These comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The sea urchin embryo is a suitable model for compound screening ( Semenova et al, 2008 , 2018 ; Lichitsky et al, 2019 ). The phenotype associated with CK-666 mediated Arp2/3 inhibition ( Sepúlveda-ramírez et al, 2018 ) was confirmed here with two other Arp2/3 inhibitory compounds.…”
Section: Discussionmentioning
confidence: 99%
“…The sea urchin embryo is a suitable model for compound screening ( Semenova et al, 2008 , 2018 ; Lichitsky et al, 2019 ). The phenotype associated with CK-666 mediated Arp2/3 inhibition ( Sepúlveda-ramírez et al, 2018 ) was confirmed here with two other Arp2/3 inhibitory compounds.…”
Section: Discussionmentioning
confidence: 99%
“…2-Hydrazinobenzimidazolе was synthesized according to the published method. 26 1-Hydrazinophthalazine hydrochloride (hydralazine) (98%) and 2,6-diacetylpyridine (99%) were acquired from Alfa Aesar. Copper salts (98%) were purchased from Alfa Aesar.…”
Section: Reagents and Materialsmentioning
confidence: 99%
“…For example, pyrazolo­[3,4- b ]­pyridin-6-ones were first synthesized by condensation of ethylidenemalonic acid diethyl ester and 1-ethyl-5-amino-methylpyrazole . Moreover, the synthesis of pyrazolo­[3,4- b ]­pyridin-6-one derivatives by a three-component reaction of an aldehyde, Meldrum acid, and aminopyrazole under various conditions , and with organic and inorganic catalysts (Scheme , i-(a) and i-(b)) has been reported previously, but no asymmetric version has been disclosed. In 2011, Chkanikov and co-workers synthesized 6,7-dihydro-1 H -pyrazolo-[3,4 b ]-pyridin-6-ones with 4-ArSCF 2 and 4-ArSCHF groups by direct annulation of 1-substituted 5-aminopyrazoles with ethyl 4,4-difluoro-4-phenylthioacetoacetate (Scheme , i-(c)) .…”
mentioning
confidence: 99%